2018
DOI: 10.3390/ijerph15081681
|View full text |Cite
|
Sign up to set email alerts
|

Association of Self-Perceived Oral Health and Function with Clinically Determined Oral Health Status among Adults Aged 35–54 Years: A Cross-Sectional Study

Abstract: This study aimed to analyse the association of self-perceived oral health status (OHS) and functions with clinical OHS in Korean adults aged 35–54 years. The study was designed as a cross-sectional study using data from the Fourth Korea National Health and Nutrition Examination Survey (2007–2009). A total of 6605 subjects aged 35–54 years who completed the oral examination and questionnaires were included. An association of self-perceived OHS and functions with clinically determined OHS was confirmed by a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 29 publications
1
25
1
2
Order By: Relevance
“…4 In previous studies, SROH has shown a high reliability with clinical oral health outcomes. 32 Thus, SROH is regarded as a practical and easily interpreted measure to assess inequalities in the oral health of a population. 11,12,33,34 We confirmed the same patterns of the outcome variable through a sensitivity analysis and robustness check.…”
Section: Discussionmentioning
confidence: 99%
“…4 In previous studies, SROH has shown a high reliability with clinical oral health outcomes. 32 Thus, SROH is regarded as a practical and easily interpreted measure to assess inequalities in the oral health of a population. 11,12,33,34 We confirmed the same patterns of the outcome variable through a sensitivity analysis and robustness check.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] In a study from the KNHANES IV, self-perceived oral health status and function were strongly associated with clinical oral health status, which included the number of untreated decayed teeth (B = 0.405, P < .001); number of decayed, missing, and filled teeth (B = 0.126, P < .001); prosthesis scores (B = 0.691, P < .001); and periodontal scores (B = 0.700, P < .001), as determined by trained dentists. [ 10 ] Using self-rated oral health in population surveys is a more valid, reliable, and cost-effective measure than carrying out examinations, as it can quickly identify the state of the populations oral health and associated factors. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…In the last 2 decades, studies have reported on the relationship between oral and general health as well as identified factors associated with reported health status. [1][2][3][4][5] An analysis of available new data on the topic provides an opportunity to expand the literature by providing more current evidence on this relationship, given its importance for policy and program development, and dental public health practice. In addition, measures of general and oral health have the potential to demonstrate a linear change when oral and general health are measured directly with other closely related variables.…”
Section: Introductionmentioning
confidence: 99%